Modification of the existing maximum residue levels for metaldehyde in flowering brassica and leafy brassica - European Food Safety Authority (EFSA); Giulia Bellisai; Giovanni Bernasconi; Alba Brancato; Luis Carrasco Cabrera; Irene Castellan; Monica Del Aguila; Lucien Ferreira; German Giner Santonja; Luna Greco; Samira Jarrah; Renata Leuschner; et al. (EFSA Journal)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Glanzit Pfeiffer Gmbh & Co. KG submitted a request to the competent national authority in Germany to modify the existing maximum residue levels (MRLs) for the active substance metaldehyde in flowering brassica and leafy brassica. The data submitted in support of the request were found to be sufficient to derive MRL proposals for both brassica crop groups. Adequate analytical methods for enforcement are available to control the residues of metaldehyde on the commodities under consideration at the validated limit of quantification (LOQ) of 0.05 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the intended uses of metaldehyde according to the reported agricultural practices is unlikely to present a risk to consumer health. The long‐term consumer risk assessment shall be regarded as indicative only due to the data gaps identified for certain existing MRLs in the framework of the MRL review of metaldehyde according to Article 12 of Regulation (EC) No 396/2005.